Current insights on m6A RNA modification in acute leukemia: therapeutic targets and future prospects - Kaur, Parminder; Sharma, Pankaj; Bhatia, Prateek; Singh, Minu (Frontiers in Oncology, 2024)
RNA modification is the critical mechanism for regulating post-transcriptional processes. There are more than 150 RNA modifications reported so far, among which N6-Methyladenosine is the most prevalent one. M6A RNA modification complex consists of ‘writers’, ‘readers’ and ‘erasers’ which together in a group catalyze, recognize and regulate the methylation process of RNA and thereby regulate the stability and translation of mRNA. The discovery of erasers also known as demethylases, revolutionized the research on RNA modifications as it revealed that this modification is reversible. Since then, various studies have focused on discovering the role of m6A modification in various diseases especially cancers. Aberrant expression of these ‘readers’, ‘writers’, and ‘erasers’ is found to be altered in various cancers resulting in disturbance of cellular homeostasis. Acute leukemias are the most common cancer found in pediatric patients and account for 20% of adult cases. Dysregulation of the RNA modifying complex have been reported in development and progression of hematopoietic malignancies. Further, targeting m6A modification is the new approach for cancer immunotherapy and is being explored extensively. This review provides detailed information about current information on the role of m6A RNA modification in acute leukemia and their therapeutic potential.